Isolated Palpebral Tuberculosis - Gonzague, Miray Louis De; Rindra, Rafanomezantsoa; Dinaniaina, Rakotonirina Vero Herinjaka; Mihaja, Ramanarivo Norotiana; Andry, Rakotoarivelo Rivonirina; Léa, Raobela (Journal of Ophthalmology and Research, 2021)
Tuberculosis is highly prevalent in Madagascar and virtually all the patients were infected in the cours of their childhood. Cutaneous tuberculosis is a rare condition which accounts for 1% to 2% of all cases of tuberculosis. Worldwide eyelid tuberculosis is underreported in Madagascar. We report a case of 13-year-old male patient presenting a prolapsed granuloma and papillomatous lesion in external part of the right upper eyelid conjunctiva. Histopathological findings show Malpighian epithelium ulceration. The chorion was the site of granulomatous inflammatory infiltrate, epithelioid with giant cells in hematoxylin and eosin stain. There were no granulomas, caseous necrosis. The diagnosis of follicular tuberculosis is posed. An excellent response was seen with antitubercular therapy with complete eyelid wound healing. In the face of chronic lesion of eyelid, including granuloma, ulcer as well as a swelling even a lesion mimicking a chalazion, histology is crucial to detect tuberculosis.